2020
DOI: 10.1002/ange.202001634
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Energy Transfer from Ruthenium Complexes to Chiral Eniminium Ions: Enantioselective Synthesis of Cyclobutanecarbaldehydes by [2+2] Photocycloaddition

Abstract: Chiral eniminium salts, prepared from a,b-unsaturated aldehydes and a chiral proline derived secondary amine, underwent, upon irradiation with visible light, a rutheniumcatalyzed (2.5 mol %) intermolecular [2+2] photocycloaddition to olefins, which after hydrolysis led to chiral cyclobutanecarbaldehydes (17 examples, 49-74 % yield), with high diastereo-and enantioselectivities. Ru(bpz) 3 (PF 6 ) 2 was utilized as the ruthenium catalyst and laser flash photolysis studies show that the catalyst operates exclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…As demonstrated by Yoon and co-workers, Lewis acids can significantly decrease excited-state energies, 39 which is likely expandable to further classes of substrates or activators, as already demonstrated by LUMO lowering of enones through eniminium ion formation. 40 This merger of the unique reactivity modes of photo-and Lewis acid catalysis or amine organocatalysis underlines the value of dual catalytic approaches (Figure 7). Within the recent years, dual-EnT catalysis has emerged not only to activate otherwise unreactive substrate classes but also to enable novel synthetic (dis)connections.…”
Section: Perspectives and Directionsmentioning
confidence: 89%
See 1 more Smart Citation
“…As demonstrated by Yoon and co-workers, Lewis acids can significantly decrease excited-state energies, 39 which is likely expandable to further classes of substrates or activators, as already demonstrated by LUMO lowering of enones through eniminium ion formation. 40 This merger of the unique reactivity modes of photo-and Lewis acid catalysis or amine organocatalysis underlines the value of dual catalytic approaches (Figure 7). Within the recent years, dual-EnT catalysis has emerged not only to activate otherwise unreactive substrate classes but also to enable novel synthetic (dis)connections.…”
Section: Perspectives and Directionsmentioning
confidence: 89%
“…In this case, the Lewis acid not only induces chirality but also lowers the olefin triplet energy through bidentate coordination, thereby ''switching on'' the initial EnT event (Figure 3B). 39 Similarly, Bach and co-workers 40 demonstrated how covalent pre-activation (through iminium formation) allows for activating acyclic enones for sensitized (enantioselective) cycloadditions.…”
Section: Sensitization Of Olefinsmentioning
confidence: 99%
“…Notably, a p-alkoxy-substituted styrene (20) was tolerated under these conditions, whereas the same alkene undergoes rapid polymerization using our previous Lewis acid-catalyzed methods 11 . Various functional groups including protected alcohols (22)(23), a photolabile azide (24), and a protected amine (25) were all tolerated. Heterocycles were also readily transformed including benzofuran-and indole-substituted alkenes (28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…Pioneering studies by Melchiorre and colleagues 19,20 have demonstrated that secondary amine organocatalysts can activate prochiral enals by chromophore activation: the iminium intermediates absorb at longer wavelengths than the free enal substrates and the excited states have been utilized in a variety of useful organic transformations. Very recently, Bach and colleagues 21,22 demonstrated the first example of triplet activation by secondary amine organocatalysis, demonstrating that the vinyl iminium intermediate undergoes energy transfer faster than the free parent enal and can be the key intermediate in an enantioselective [2 + 2] photocycloaddition. The ability of Brønsted acid catalysts to engage in chromophore and triplet activation mechanisms, however, has been underexplored.…”
mentioning
confidence: 99%
“…The next step involves energy transfer from the triplet photosensitiser to the substrate in an overall spin-allowed process that returns the photosensitiser to the S0 level and simultaneously promotes the substrate from S0 to the reactive T1 state, which can then undergo a variety of intra-and intermolecular processes. 2,3 Enantioselective versions of photochemical reactions have been developed through dual catalytic strategies that combine an achiral photosensitiser with a photochemically inactive chiral catalyst (Figure 1C), [12][13][14] or by employing chiral photosensitisers (Figure 1D). 10,15 Although powerful, these approaches do not offer a general solution, and many desirable photochemical processes are not amenable to enantioselective catalysis.…”
Section: Introductionmentioning
confidence: 99%